A bridge between the smart grid and the Internet of Things: Theoretical and practical roles of LoRa. (December 2019) - Hwang, Lain-Chyr; Chen, Chao-Shun; Ku, Te-Tien; Shyu, Wei-Cheng
Highlights: The deployment of LoRaWAN should be planned theoretically and assistant with measurements. A channel model features propagation attenuation, shadowing effect, and multipath fading. The theoretical model is used to develop an APP that can estimate the transmission distance of LoRa. The feasibility of this APP is verified by practical measurements. The results show that the model and APP are feasible. Abstract: Most IoT technologies can make smart grids smarter, and LoRa is an emerging technology suitable for smart grids. The development of LoRa and the deployment of LoRaWAN, however are not mature. This study will investigate LoRa and support the deployment of LoRaWAN in smart grids. Trial and error is not sufficient for deployment of LoRaWAN, and it should be planned using theoretical approaches, assisted by measurements. Therefore, this work uses theoretical considerations to develop a channel model of LoRa that considers propagation attenuation, shadowing effect, and multipath fading. The theoretical model is used to develop an APP that can estimate the transmission distance of LoRa. To verify the feasibility of this APP, experiments use different parameters for the environment and transmission. Each experiment gives a packet error rate for transmission between two nodes. The packet error rate is obtained by measurement, and the distance between nodes is estimated theoretically. Results show that the model and the APP are feasible. This study also finds that the effect of a spreading factor is not as great as proposed by theory. Three factors affect the performance of LoRa, where distance is the main factor and obstacles and noise produce randomness. The contribution of this work is twofold. One is the theoretical channel model and the other is the practical APP. The engineers who are in charge of planning LoRaWAN can use the feasible APP to accelerate the progress of deployment.